Nutritional and phytogenic properties of pawpaw (Carica papaya) leaf meal on blood characteristics of growing rabbits - Peter-Damian Chukwunomso Jiwuba; Ogechi Evangeline Kadarumba (Acta Fytotechnica et Zootechnica, 2019)
The study aimed to examine the effect of pawpaw (Carica papaya) leaf meal diets on blood characteristics of rabbits. A total of 48, male rabbits were randomly divided into four experimental groups of twelve animals each, with four rabbits constituting a replicate. Each group was assigned to one of the experimental diets containing pawpaw leaf meal (PLM) at 0% (control), 15%, 30% and 45% for 56 days in a completely randomized design (CRD). Blood samples for analysis were obtained from each replicate and data obtained were analyzed statistically. Results on chemical composition of the PLM revealed 87.67% DM, 17.30% CP, 12.86% CF, 8.88% ash, 0.81% EE 47.82% NFE and 2348.05 Kcal/kg ME. PLM at 15% inclusion increased (P <0.05) the packed cell volume (PCV) and haemoglobin (Hb) when compared with the control. PLM at 30 and 45% resulted to improved mean cell volume (MCV) concentration. The concentrations of white blood cells were increased (P < 0.05) at the treatment (15%, 30% and 45%) groups. Red blood cell, mean cell volume, mean cell haemoglobin concentration, creatinine, AST, ALP, sodium, potassium and chloride remained similar (P > 0.05) across the treatments. Total protein was however best (P < 0.05) at 45% supplementation. The results indicated that PLM enhanced haemopoiesis and health status of the experimental rabbits and therefore should be incorporated into rabbit feeding to enhance blood formation and health status of the animals.